Model Pembelajaran Interaktif dapat Meningkatkan Prestasi Belajar Siswa Kelas III SD Negeri 7 Metro Pusat dalam Pembelajaran IPS Tentang Lingkungan Alam dan Buatan Semester I Tahun Ajaran 2012/2013 - Toti HS (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
This classroom action research aims to analyze the interest and student learning outcomes in social studies about the natural environment and the built environment through interactive learning model. Procedures action research consisted of two cycles. Each cycle is implemented in accordance with the change to be achieved. Implementation of this class action using the following procedure: action planning, action, observation, and reflection. The planning stage is started with the holding debriefing and discussion of the natural environment and the built environment, set up RPP (Lesson Plan) to be used as a reference in the implementation of measures in cycle I. Implementation of the first cycle of learning that the teacher explains the material and then held a question and answer to students , guide students in doing LKS, and discuss LKS to measure students' ability to accept the teacher's explanation. Based on the results of formative tests pasa cycle I obtained an average value of 6.9 and graduation niali KKM amounted to 65.2%. On the implementation of the first cycle of learning, apparently the result of evaluation of student learning shows that an understanding of the natural and artificial environment is still lacking for the teachers make learning improvement plan in accordance with set improvement goals. Based on the factors that cause less successful learning social studies teacher design a plan in general in implementing the improvement of learning, namely: to hold a dialogue with Shiva discussing the natural environment and the built environment with a sentence coherently, create a worksheet, use a learning method that varies the lecture method, question and answer method, discussion method, and the method of administration tasks. After the attempted improvements in cycle II learning through interactive learning model is then formative II test results obtained by the average value of 7.8 with the graduation of 87% KKM action results in the second cycle showed a satisfactory success.